Complete mitochondrial genome of Leptaulax koreanus (Coleoptera: Passalidae), a Korean endemic bess beetle - Seung-Gyu Lee; Kyoung Su Choi; Chang-Jun Kim; Hyung-Bae Jeon; Il-Kwon Kim (Mitochondrial DNA. Part B. Resources, 2019)
In the present paper, we make a first report on the complete mitochondrial DNA genome of Leptaulax koreanus, a Korean endemic species, in Passalidae. The mitogenome is 18,730 base pairs with 13 protein-coding genes, 22 tRNAs, 2 rRNAs, and a 4240 bp long AT-rich region. The overall base composition is 78.4% AT and 21.6% GC. The maximum likelihood analysis suggested that L. koreanus is a sister to other Scarabaeoidea species.